2010
DOI: 10.1177/0890334410390046
|View full text |Cite
|
Sign up to set email alerts
|

“They’ve Walked in My Shoes”: Mothers of Very Low Birth Weight Infants and Their Experiences With Breastfeeding Peer Counselors in the Neonatal Intensive Care Unit

Abstract: The effectiveness of the breastfeeding peer counselor role is thought to be embedded in the relationship between new and experienced mothers. In this study, new mothers of very low birth weight infants emphasized that one of the most important aspects of their relationship with the breastfeeding peer counselors is the peer or shared experience of how difficult it can be to provide milk and breastfeed while coping with the emotional stress of having an infant in the neonatal intensive care unit. This study prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
95
0
8

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(115 citation statements)
references
References 45 publications
5
95
0
8
Order By: Relevance
“…2027 In a prospective cohort study, Hoban et al reported that mothers of very low birthweight (VLBW; <1500 grams birthweight) infants changed their HM feeding goals over the course of the NICU hospitalization, and became increasingly unlikely to achieve their goals for exclusive or partial HM as the hospitalization progressed. 14 It has been proposed that the profound dislike and inconvenience of long-term HM expression, maternal stress and fatigue, insufficient encouragement and assistance from family and friends, and inconsistent advice in the NICU all play a role in mothers’ discontinuation of HM provision prior to NICU discharge.…”
Section: Initiation and Maintenance Of Lactation In Mothers Of Pretermentioning
confidence: 99%
See 1 more Smart Citation
“…2027 In a prospective cohort study, Hoban et al reported that mothers of very low birthweight (VLBW; <1500 grams birthweight) infants changed their HM feeding goals over the course of the NICU hospitalization, and became increasingly unlikely to achieve their goals for exclusive or partial HM as the hospitalization progressed. 14 It has been proposed that the profound dislike and inconvenience of long-term HM expression, maternal stress and fatigue, insufficient encouragement and assistance from family and friends, and inconsistent advice in the NICU all play a role in mothers’ discontinuation of HM provision prior to NICU discharge.…”
Section: Initiation and Maintenance Of Lactation In Mothers Of Pretermentioning
confidence: 99%
“…2325,27,31–34 However, many breast pump-dependent mothers of preterm infants have chronic health problems or pregnancy and birth complications that impact lactation outcomes and that may be unresponsive to current behavioral and motivational interventions. 8,18,35 These complications, which include pre-pregnancy body-mass-index (BMI) >25, preterm birth, Cesarean delivery and preeclampsia, as well as prolonged bedrest and medications to treat these complications, impact the hormonal processes that regulate secretory differentiation and early lactation.…”
Section: Initiation and Maintenance Of Lactation In Mothers Of Pretermentioning
confidence: 99%
“…Hospital staff should assess the effi ciency of infants' latch and BF attempt. 2,5,30,33,34 Mothers respond to professional support regarding education about the importance of breast milk, frequency of pumping, skin-to-skin care, and transition to exclusive BF. Unit protocols differed from 1 to 3 successful BF in last 24 h. 29 , 30 Facilitate BF support by lactation consultants, peer BF counselors, and professional medical team for mothers and infants to transition to exclusive BF.…”
Section: Figurementioning
confidence: 99%
“…The low rates were likely a reflection of the high percentage of African Americans in our sample, as this population has the lowest rate of breastfeeding in the U.S. (Centers for Disease Control and Prevention, 2010). The low overall rates of both any and exclusive breastfeeding we found post-discharge are concerning for infant and maternal health and might be improved through peer counselors and other evidence-based lactation support for this population (Miracle et al, 2004; Rossman et al, 2011). …”
Section: Discussionmentioning
confidence: 85%